Genetic Aspects in Shoulder Disorders - Carina Cohen; Eduardo A. Figueiredo; Paulo S. Belangero; Carlos Vicente Andreoli; Mariana Ferreira Leal; Benno Ejnisman (Revista Brasileira de Ortopedia, 2020)
Abstract The influence of genetic inheritance has been increasingly investigated in shoulder disorders, such as rotator cuff injury, instability and frozen shoulder. Although the initial findings are enlightening, it is necessary to progressively build a database of genetic markers to catalog genomic profiles that, later, may contribute for predicting the risk of the disease, as well as to the development of better diagnostic and treatment tools. The present article seeks to update what is evidence of genetic studies in the literature for these diseases, from polymorphism analyses, expression of candidate genes in tissues and broad genomic association studies (GWAS). However, it is necessary to point out that there is great difficulty in replicating and using the findings, mainly due to the lack of statistical power, the high rate of false-positive results and the large number of variables involved.